Emotional intelligence and institutional climate according to the perception of the teachers of the I.S.P.P “Marcos Duran Martel” - Sabrera-Alva, Carmen (2023)
The objective was to determine the degree of relationship of emotional intelligence with the improvement of the institutional climate, according to the perception of teachers, in the I.S.P.P "Marcos Duran Martel" - Huánuco. The type of research was basic with a correlational level and a non-experimental design. The sample consisted of 38 I.S.P.P teachers, to whom a questionnaire validated by experts was applied and with a reliability according to Cronbach's alpha of 0.89 (emotional intelligence) and 0.81 (institutional climate). The results show that the relationship between empathy and social skills is 0.40. The relationship of social skills with assertiveness is 0.70. The correlation index shows that the value of r = 0.40 and r = 0.70, are located between 0.40 ≤ r <0.80, therefore, it is concluded that: there is a significant correlation between emotional intelligence and the improvement of the institutional climate, according to teachers' perception, in the ISPP Marcos Duran Martel.